Moxibustion treatment for Parkinson's disease: study protocol for a randomized controlled trial - Chunxiao Wu; Lijun Zhao; Yuelin Guo; Xiaoqian Hao; Yaohua Fan; Peipei Wu; Jiajun Han; Qinglian Li; Xiaoling Wang; Qizhang Wang; Xiaodong Luo; Meiling Zhu (BMC, 2023)
Abstract Background Parkinson's disease (PD) is the second most common neurodegenerative disorder and seriously affects quality of life globally. Moxibustion is widely used to treat neurodegenerative diseases in the clinic and has achieved a beneficial clinical effect. However, strict control and high-quality randomized controlled trials are still lacking. Therefore, this trial aims to evaluate the clinical efficacy and safety of moxibustion in patients with PD and preliminarily explore the underlying mechanism. Methods This is a randomized, single-blind and placebo-controlled trial design in which 70 eligible participants will be randomly divided into a moxibustion group and a sham moxibustion group. Baihui (DU20) and Sishenchong (EX-HN1) are selected for both groups. The treatment will be performed for 30 min per session, two sessions a week for 8 weeks. The mean change in MDS-UPDRS scores (including MDS-UPDRS II, III subscale scores and total scores) from baseline to the observation points will be the primary outcome. The secondary outcomes will include scores on the Parkinson's Disease Questionnaire-39 (PDQ-39), Fatigue Severity Scale (FSS), Parkinson Disease Sleep Scale (PDSS), Montreal Cognitive Assessment (MoCA), and Self-Rating Depression Scale (SDS) as well as the Wexner constipation score. All the above outcomes will be assessed at 4 and 8 weeks. Laboratory blood biochemical analysis and functional magnetic resonance imaging (fMRI) will be conducted at baseline and at the end of treatment to explore the potential mechanisms of moxibustion in regulating PD. Discussion In conclusion, the results of this trial will reveal whether moxibustion is effective for treating motor and nonmotor symptoms in PD. This trial will also preliminarily explore the underlying mechanism of the regulatory effect of moxibustion in PD, which will contribute to providing a theoretical basis for the treatment of PD. Trial registration ClinicalTrials.gov ChiCTR2000029745. Registered on 9 August 2021.